UPAYA PENCITRAAN TELEVISI LOKALÃ¢â‚¬JOGJA TV MELALUI PROGRAM SIARAN TELEVISI BERBASIS BUDAYA DAERAH - NRA. Candra DA (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
THE IMAGE BUILDING ATTEMPT OF LOCAL TELEVISION USING LOCAL CULTUREBASED TELEVISION BROADCASTING PROGRAM (A Case Study on Yogyakarta â€œJOGJA TVâ€)is basically made to investigate the essence and role of television as the mass media, technical and production principles of television broadcasting program and to capture the meaning of television broadcasting programs particularly for the local television media of Yogyakarta JOGJA TV. This research aims to find out the image construction JOGJA TV wants to build as its attempt of strengthening its position and image building for the area where this media operates its broadcasting activity. The research method employed in this research is the descriptive qualitative one. Considering the problem proposed here, this research particularly employed the communication theory approach emphasizing on disclosing the role and function of television mass media within the society as a part of the attempt of building positive image on the existence of media. The conclusion of research process series states that in confirming the positive image within the society, JOGJA TV gives more dominant local load portion as its broadcasting basic concept. The concrete manifestation is by producing and then showing the local culture-based broadcasting programs with the more dominant program composition. The basic guidelines used by JOGJA TV in its attempt of building positive image for Yogyakarta people and surrounding includes to develop company profile as the main foundation as the principle of broadcasting organization process, producing television program and conducting the societal activities such as corporate social responsibility for its audience society.Keywords: image building, JOGJA TV, culture based television programme.